Asymptotic solution of the cauchy problem for a singularly perturbed linear system - Kocherga, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct the asymptotics of the solution of the Cauchy problem for a degenerate singularly perturbed linear system in the case of multiple spectrum of the principal operator.